2013
DOI: 10.1179/1743281212y.0000000034
|View full text |Cite
|
Sign up to set email alerts
|

Influences of SEN structures on flow characters, temperature field and shell distribution in 420 mm continuous casting mould

Abstract: Ultrathick continuous slab casting is a growing technology, especially in developing countries due to the vast market demand of thick rolled plate. The structure of the submerged entry nozzle is regarded as the crucial factor to determine flow related phenomena in the mould. This article conducts a 0?55 scale water model and a three-dimensional numerical model to investigate the influences of submerged entry nozzle on flow behaviour, temperature field and solidified shell distribution in a 420 mm ultrathick sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Water modeling has been often used for analyzing flow patterns in mold . According to the similarity theory, the geometric similarity and the dynamic similarity should be guaranteed simultaneously. In the molten steel and the water model, the Froude numbers should be equal and the Reynolds numbers are needed to be in the same state (laminar or turbulent).…”
Section: Water‐model Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water modeling has been often used for analyzing flow patterns in mold . According to the similarity theory, the geometric similarity and the dynamic similarity should be guaranteed simultaneously. In the molten steel and the water model, the Froude numbers should be equal and the Reynolds numbers are needed to be in the same state (laminar or turbulent).…”
Section: Water‐model Experimentsmentioning
confidence: 99%
“…Barreto et al improved the fluid dynamics of a typical slab caster mold by redesigning the SEN ports, and it was reported that compared to the original SEN, the double‐roll flow pattern was well developed at a deeper position, and the proposed improved design maintained good free surface stability without any vortex formation. Chen et al investigated the influences of SENs on the flow behavior and temperature field of an ultra‐thick slab mold, and the tunnel bottom nozzle was considered to be the optimal, with a lively surface behavior and a favorable heat transfer. Zhao et al compared the effect of the two‐port SEN and the three‐port SEN on the level fluctuation and the heat transfer of a medium thin slab mold.…”
Section: Introductionmentioning
confidence: 99%
“…The layout of extensive thermocouples is designed to detect temperature variation in the mould copper plates. The horizontal propagation velocity is accurately computed using equation (2), and the result is shown in Fig. 14. For all of the 64 sticker samples, the minimum horizontal velocity is 0?85 m min 21 , whereas the maximum horizontal velocity is 2?25 m min 21 .…”
Section: Horizontal Propagation Velocitymentioning
confidence: 99%
“…1,2 In order to satisfy the requirements of low production costs, quality demands, slabs are required to have high strength, cleanness and toughness, fatigue resistance, good welding properties, etc. [3][4][5] Sticker breakout is a serious and common problem in steel plants and its mechanism was widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The SEN can affect the flow pattern, solidified shell growth, free surface status and inclusion removal in the CC mold [1,2]. Previous works have developed both experimental and numerical models for analyzing the flow [3][4][5] and initial solidification [6][7][8] in the CC mold under different SEN conditions. These studies found that an appropriate SEN structure cannot only enhance the flow field, but also improve the heat transfer process in the mold of both slabs and blooms significantly.…”
Section: Introductionmentioning
confidence: 99%